2019
DOI: 10.1002/tox.22830
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effects of rhein through the mitochondrial pathways, two death receptor pathways, and reducing autophagy in human liver L02 cells

Abstract: Rhein (4,5‐dihydroxyanthraquinone‐2‐carboxylic acid) is a major component of many medicinal herbs such as Rheum palmatum L. and Polygonum multiflorum. Despite being widely used, intoxication cases associated with rhein‐containing herbs are often reported. Currently, there are no available reports addressing the effects of rhein on apoptosis in human liver L02 cells. Thus, the aim of this study is to determine the cytotoxic effects and the underlying mechanism of rhein on human normal liver L02 cells. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In addition, ATG5 could promote proliferation and metastasis and inhibit breast cancer cell apoptosis [49]. A previous study found that rhein inhibited the autophagy of human cancer cells via downregulation of ATG5 [50]. Additionally, Ra EA et al indicated that TRIM31 could promote Atg5/Atg7-independent autophagy in intestinal cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ATG5 could promote proliferation and metastasis and inhibit breast cancer cell apoptosis [49]. A previous study found that rhein inhibited the autophagy of human cancer cells via downregulation of ATG5 [50]. Additionally, Ra EA et al indicated that TRIM31 could promote Atg5/Atg7-independent autophagy in intestinal cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…No studies in the broader literature have carried out on E. arenarium Guss plant extract or other species of the genus at this level of investigation. Many plants extracts have been described in the literature as having anti‐cancer properties and which inhibit cell proliferation by inducing the process of apoptosis in different ways depending on the nature of the products and on the kind of tumor cells 34 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, rhein increased ROS, tumor necrosis factor-α (TNF-α), tumor necrosis factor receptor (TNFR), and TRADD, cleaved caspase-3, and reduced MMP and pro-caspase-9 and -3. Notably, the decrease in the levels of the autophagy-related proteins LC3-II and Beclin-1 and increase in the expression of P62 indicated that rhein promoted apoptosis of L02 cells by inhibiting autophagy and decreasing their self-scavenging ability ( Li et al, 2019 ).…”
Section: Active Ingredients Of Rhei Radix Et Rhizoma Used For Hcc Tre...mentioning
confidence: 99%